Phycoremediation of waste water from a plastic manufacturing industry with Chlorella pyrenoidosa H.Chick in laboratory study - Kenanga Sari; Tri Retnaningsih Soeprobowati; Riche Hariyati (Waste Technology, 2014)
Abstrack - The plastic industries has increased by 7-8% per year, it will cause a negative impact for the environment. The wastewater of plastic industrial contain many pollutants such as hazardous substances bensen, formaldehyde and heavy metals (Cd, Cu, Cr and Pb). Heavy metals Cu is the most dangerous heavy metals since Cu can inhibit enzyme systems, remediation are needed to reduce the pollutants in the environment. One effective way is by using Chlorella pyrenoidosa H.Chick as phycoremediation agent. This study aims to assess the percentage of population growth and decline of heavy metals Cu after inoculation with C. pyrenoidosa H.Chick. The method used is to cultivate C. pyrenoidosa H.Chick in plastic wastewater for 8 days and observed a decrease of percentage heavy metal Cu and population growh of C.pyrenoidosa H.Chick. Environmental factors such as temperature, salinity, pH, light intensity is maintained in order to remain stable. The data obtained with T test. After 8 days of the study turned out that C. pyrenoidosa H.Chick able to reduce Cu of 0.435 mg / l to 0.24 mg / l within 8 days and decrease percentage is 44.83%, thus meeting the criteria of the quality standard of waste according to the PP. 82 of 2001 in the amount of 0.2 ppm and safe for environment. Keywords: Chlorella pyrenoidosa, phycoremediation, water, plastic, copper.